174k views
4 votes
Can someone please help me with this question? I REALLY need help.

What is the value of
$ \sum_(n=1)^\infty (\tan^(-1)√(n)-\tan^(-1)√(n+1))$? The answer should be in radians.

2 Answers

4 votes

The sum telescopes. Consider the N-th partial sum of the series,


S_N=\displaystyle\sum_(n=1)^N\bigg(\tan^(-1)\sqrt n-\tan^(-1)√(n+1)\bigg)


S_N=\bigg(\tan^(-1)\sqrt1-\tan^(-1)\sqrt2\bigg)+\bigg(\tan^(-1)\sqrt2-\tan^(-1)\sqrt3\bigg)+\bigg(\tan^(-1)\sqrt3-\tan^(-1)\sqrt4\bigg)+\cdots+\bigg(\tan^(-1)\sqrt N-\tan^(-1)√(N+1)\bigg)

Notice how
\tan^(-1)\sqrt2 is added, then immediately subtracted. The same goes for
\tan^(-1)\sqrt3, then
\tan^(-1)\sqrt4, and so on, up to
\tan^(-1)\sqrt N. This leaves us with


S_N=\tan^(-1)\sqrt1-\tan^(-1)√(N+1)

The value of the given sum is obtained as
N\to\infty. We get


\displaystyle\sum_(n=1)^\infty\bigg(\tan^(-1)\sqrt n-\tan^(-1)√(n+1)\bigg)=\lim_(N\to\infty)S_N=\tan^(-1)1-\lim_(N\to\infty)\tan^(-1)√(N+1)

To compute the limit, recall that
\tan^(-1)x has a range of
\left(-\frac\pi2,\frac\pi2\right); in particular,
\tan^(-1)x\to\frac\pi2 as
x\to\infty. So we have


\displaystyle\sum_(n=1)^\infty\bigg(\tan^(-1)\sqrt n-\tan^(-1)√(n+1)\bigg)=\frac\pi4-\frac\pi2=\boxed{-\frac\pi4}

3 votes

Answer:

-45

Explanation:

The question is asking for the sum of the sequence. Therefore, there is no such thing as a "radians" answer.

When you evaluate the sum, you should get -45 as your answer. To find so, you simply plug in 1 as n and other numbers then add the result.

User Falconspy
by
4.9k points